Importance Developing E-Learning For High School Students In Sragen Regency, Central Java - Chatarina Muryani; Sarwono Sarwono; Setya Nugraha (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
In the current era of IT advancement, innovation in the field of learning needs to be done. Besides improving the quality of learning, the use of IT in education can increase student interest in the subjects. This research is the analysis stage of developing Geography e-learning for Senior High School in Sragen Regency using ADDIE model. Data collection was done by interview using questionnaires toward 20 teachers and 416 students in 11 public and private Senior High Schools in Sragen Regency.The results of the analysis of geography teachers respons indicate that most of the geography teachers in Sragen regency were well-informed and had utilized IT in classroom learning, adding learning resources from the internet and other sources, willing to teach using e-learning, expecting e-learning material equipped with maps, imagery, video and animation which was developed. From the analysis of the students respons, students argued that most of the geography teachers in Sragen Regency had utilized the learning resources and learning media from the internet and use varied learning models. Nevertheless, there are 36% who think that geography lesson was boring and most students agreed to use e-learning for geography lesson. The main obstacle in e-learning lesson in Sragen regency was the availability of computer facilities and internet network, especially in private schools.Keywords: e-learning, readiness, geography, Senior High School